Pemanfaatan Tumbuhan Sebagai Obat Tradisional Oleh Masyarakat Kampung Momiwaren, Papua Barat - Siburian, Rima Herlina; Angrianto, Rusdy (Universitas Muhammadiyah Sorong, 2024)
Momiwaren Village is one of the villages close to the Momiwaren Protected Forest Area. In line with regional development and technological advances, knowledge of the use of plants as medicinal ingredients is starting to disappear. For this reason, it is necessary to conduct research on how many types of plants are still used by the community as medicinal ingredients. The method used in this research is a survey method with interview techniques. The results of this research show that the people of Momiwaren Village still use plants as medicinal ingredients. There are 30 species from 22 families used by the community. If we look at the conservation status of the plants used, the types of plants used are still included in the naturally available (LC/DD) category, but there is one type of plant that is threatened with extinction and requires further silvicultural action so that this plant can be cultivated and not extinct from nature.